Sex-lethal autoregulation requires multiple cis-acting elements upstream and downstream of the male exon and appears to depend largely on controlling the use of the male exon 5' splice site. - Horabin, J.I.; Schedl, P. (Molecular and Cellular Biology, 1993)
The on/off state of the binary switch gene Sex-lethal (Sxl), which controls somatic sexual development in Drosophila melanogaster, is regulated at the level of alternative splicing. In males, in which the gene is off, the default splicing machinery produces nonfunctional mRNAs; in females, in which the gene is on, the autoregulatory activity of the Sxl proteins directs the splicing machinery to produce functional mRNAs. We have used germ line transformation to analyze the mechanism of default and regulated splicing. Our results demonstrate that a blockage mechanism is employed in Sxl autoregulation. However, in contrast to transformer, in which Sxl appears to function by preventing the interaction of splicing factors with the default 3' splice site, a different strategy is used in autoregulation. (i) Multiple cis-acting elements, both upstream and downstream of the male exon, are required. (ii) These cis-acting elements are distant from the splice sites they regulate, suggesting that the Sxl protein cannot function in autoregulation by directly competing with splicing factors for interaction with the regulated splice sites. (iii) The 5' splice site of the male exon appears to be dominant in regulation while the 3' splice site plays a subordinate role.